"Marketing from the Art World": A Critical Review of American Research in Arts Marketing. Issue 1 (1st January 2017) - Lee, Jin Woo; Lee, Soo Hee
ABSTRACT: The purpose of this article is to provide an integrative review and future directions for research in arts marketing by highlighting the social and cultural mechanisms by which marketing research can be inspired, especially in the context of contemporary arts. We categorize previous research in arts marketing into three perspectives: Marketing of Arts Organizations; Marketing with Artworks/Artists; and Marketing from the Art World. With these three categories, this article also examines recent developments in the contemporary art market to discover emerging trends and issues. The primary contribution of the article lies in identifying Marketing from the Art World as a new perspective from which to explore central issues of marketing associated with the uncertainty and fluidity of the contemporary art market.